Sistematización, de la experiencia artístico pedagógica del curso danza Litoral Pacífico 2023-1-UAN. (2024)
This systematization is part of a reflection on the impact of theoretical-practical experiences in the construction of the knowledge of the master artist, based on the programmatic content developed in the Litoral Pacífico dance course 2023-I, of the Bachelor's Degree in Performing Arts program of the Antonio Nariño University. The main objective is to systematize the pedagogical artistic experience to the current state of tradition (EAPEAT) in the Telembí Triangle (Nariño) in 2023-1, for the recognition of the contributions to the training process of the students. It is theoretically organized in three categories: importance of the curricular contents in the training of the master artist, applicability of the theoretical-practical knowledge acquired for the training of the master artist and the experience in the formative narrative of the master artist, as a research process.